New Galumnoidea (Acari, Oribatida) from Hanoi (Northern Vietnam) - Ermilov, Sergey G.; Starý, Josef (Zootaxa, 2018)
Three new species of oribatid mites of the superfamily Galumnoidea (Acari, Oribatida) are described from vicinities of the city of Hanoi in Northern Vietnam. Allogalumna bochkovi sp. nov. differs from all species of the genus Allogalumna by the spindle-shaped bothridial setae having very long, setiform apex. Trichogalumna mironovi sp. nov. differs from all species of the genus Trichogalumna by the presence of a large quadrangular protruding rostrum and strong ridges of different form in median part of notogaster and anogenital region, and the absence of notogastral porose areas Aa. Galumnella paracellularis sp. nov. differs from G. cellularis Balogh & Mahunka, 1967 by the larger body size and reticulate prodorsum.